Comparative study of consultant psychiatrist and clinical psychologist among psychiatric patients, using Rorschach test - Yengkokpam, B; Shah, SK; Bhantana, GR; Giri, P (Journal of College of Medical Sciences-Nepal, 2010)
This comparative study among psychiatric patients attending College of Medical Sciences, teaching hospital, Bharatpur, Nepal was carried out to determine responses on Rorschach test (RT). A total of 65 diagnosed psychiatric patients as per international classification of diseases (ICD-10) criteria attending psychiatric OPD between ages of 15 to 65 years, both male and female in the period of January 2009 to July 2009 were selected. RT was administered and results were tabulated as per diagnosis by clinical psychologist. Out of total 65 patients who underwent RT, 41 were male and 24 were female in the ratio of 63:37. In clinical psychologist diagnosis- 38 were schizophrenia, 7 were psychotic depression, 6 were depression, 3 were mania, 1 was organic psychosis and 10 were underlying psychosis and in consultant psychiatrist diagnosis- 36 were schizophrenia, 5 were psychotic depression, 12 were depression, 8 were mania, 3 were organic psychosis, 1 was underlying psychosis. Key words: Rorschach test; international classification of diseases; psychotic depression; organic psychosis; underlying psychosis. DOI: 10.3126/jcmsn.v6i1.3597 Journal of College of Medical Sciences-Nepal, 2010, Vol. 6, No. 1, 14-17